every equations the the type ax^2+bx+c=0 deserve to be resolved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula provides two solutions, one as soon as ± is addition and one when it is subtraction.

You are watching: X^2+6x+4


This equation is in typical form: ax^2+bx+c=0. Instead of 1 because that a, -6 because that b, and -4 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
*

displaystylex=3+sqrt13,3-sqrt13 Explanation: displaystylex^x-6x-4=0 perfect the square way that we will pressure a perfect square trinomial top top the left ...
(2x2)-(6x)-4=0 Two options were found : x =(3-√17)/2=-0.562 x =(3+√17)/2= 3.562 action by step solution : action 1 :Equation at the end of action 1 : (2x2 - 6x) - 4 = 0 step 2 : action 3 ...
3x2-6x-4=0 Two remedies were discovered : x =(6-√84)/6=1-1/3√ 21 = -0.528 x =(6+√84)/6=1+1/3√ 21 = 2.528 step by action solution : step 1 :Equation at the end of action 1 : (3x2 - 6x) - 4 = 0 ...
The roots aredisplaystylefrac3+sqrt295ordisplaystylefrac3-sqrt295 .Explanation: displaystylex=frac-b±sqrtb^2-4ac2a ...
9x2-6x-4=0 Two services were discovered : x =(6-√180)/18=(1-√ 5 )/3= -0.412 x =(6+√180)/18=(1+√ 5 )/3= 1.079 step by step solution : action 1 :Equation in ~ the end of action 1 : (32x2 - 6x) - 4 = ...
18x2-6x-4=0 Two solutions were discovered : x = -1/3 = -0.333 x = 2/3 = 0.667 action by step solution : step 1 :Equation in ~ the end of step 1 : ((2•32x2) - 6x) - 4 = 0 action 2 : step 3 ...
More Items
*
*

*
*
*

All equations the the form ax^2+bx+c=0 can be resolved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula provides two solutions, one once ± is addition and one once it is subtraction.
This equation is in conventional form: ax^2+bx+c=0. Substitute 1 for a, -6 because that b, and -4 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one deserve to be addressed by perfect the square. In bespeak to complete the square, the equation must very first be in the kind x^2+bx=c.
Divide -6, the coefficient that the x term, by 2 to obtain -3. Then add the square the -3 to both political parties of the equation. This step renders the left hand next of the equation a perfect square.
Factor x^2-6x+9. In general, when x^2+bx+c is a perfect square, the can always be factored together left(x+fracb2 ight)^2.

See more: What Do Exclamation Marks Mean In Math ? What Does An Exclamation Mark Mean In Mathematics


Quadratic equations such together this one have the right to be fixed by a new direct factoring an approach that does not call for guess work. To use the straight factoring method, the equation must be in the type x^2+Bx+C=0.
Let r and also s it is in the components for the quadratic equation such that x^2+Bx+C=(x−r)(x−s) where sum of components (r+s)=−B and also the product of components rs = C
Two numbers r and s sum up to 6 specifically when the mean of the two numbers is frac12*6 = 3. You can likewise see the the midpoint of r and also s coincides to the axis of the opposite of the parabola stood for by the quadratic equation y=x^2+Bx+C. The values of r and also s space equidistant native the center by an unknown amount u. Express r and also s v respect to change u.
*
*

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు